Effect of selected variables on abr - K.C. Ravishankar, K.R. Chandrashekar, K.N. Shashidhar (Journal of All India Institute of Speech and Hearing, 1970)
The clinical application of the autitory brainstem response (ABR) has provided a unique diagnostic dimension that has transcended interdisciplinary boundaries (Jacobson, 1985). As a result, the use of ABR in Audiology and Ear, nose & throat clinics is gaining popularity. With the availability ofequipment and the simplicity in procedures in recent years many centers are equipping themselves with ABR instruments. It is well known that the ABR is one of the important tools in the test battery of the audiologist and has become an acceptable procedure.